Bio-cementation of sand using enzyme-induced calcite precipitation: Mechanical behavior and microstructural analysis - Gitanjali, Amali; Jhuo, Yu-Syuan; Yeh, Fu-Hsuan; Ge, Louis (Construction & building materials, 2024)
The enzyme-induced calcite precipitation (EICP) has recently gained popularity as a ground improvement technique. Bio-cementation via EICP increases the strength, stiffness, and soil liquefaction resistance by clogging the voids and binding the soil particles with calcium carbonate. The objectives of the study involve assessing the mechanical behavior of the EICP-treated sand by performing monotonic consolidated drained triaxial and undrained cyclic triaxial tests. This study adopted a one-phase EICP cementation solution consisting of 1 M Urea, 0.67 M Calcium chloride dihydrate, and 3 g/l urease enzyme. The monotonic triaxial tests on pure sand and EICP-treated sand with 3,7, and 14 curing days were carried out at 50, 100, and 200 kPa confining pressures, respectively. A noticeable effective cohesion was observed for EICP-treated sand for all curing durations. Undrained cyclic triaxial tests on the EICP-treated specimens with 7 days of curing were performed at an effective confining pressure of 100 kPa. As expected, the number of cycles to liquefaction was higher in the EICP-treated specimen compared to pure sand due to the cementation effect. Finally, scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) mapping confirmed the enhanced liquefaction resistance in EICP-treated sand due to calcium carbonate precipitation, leading to particle-to-particle interlocking. Additionally, X-ray Diffraction (XRD) analysis revealed the presence of calcite crystals resulting from the EICP treatment. •A one-phase EICP treatment for sandy specimen preparation was developed.•A noticeable effective cohesion was observed for EICP-treated sand.•SEM and EDS confirmed the liquefaction resistance enhancement.